Brazil : Financial Sector Assessment Program-Technical Note on Systemic Liquidity Management. (IMF Staff Country Reports; Country Report ;, 2018)
Brazil's financial markets are generally liquid and sophisticated. Brazil is blessed with a wide array of instruments which investors can use to manage and hedge interest rate and FX risks. The infrastructure supporting markets appears sound and is widely attributed by market participants to ensuring the resiliency of Brazil's markets despite a multitude of significant shocks. A key foundation of the resiliency of Brazil's markets is the large structural liquidity surplus (around 20 percent of GDP) and Brazil's substantial FX reserves. Market participants generally have ample cash reserves that provide a key buffer against liquidity shocks. Brazilian investors have a strong preference for high quality short term liquid investments. Brazil's history of economic instability drives investors towards short term liquid investments of the highest credit quality such as overnight repos and short-term government bonds. Dollarization is low reflecting restrictions on FX investments available within Brazil but hedges against FX risk are widely available and give investors' confidence to hold Real. Government bonds are the centerpiece of the securities markets.